Structural brain changes in patients with rheumatoid arthritis - Wartolowska, K; Hough, MG; Wordsworth, P; Tracey, I (2009)
Introduction: Recent studies demonstrated that chronic pain leads to possible structural brain changes in diseases such as lower back pain, migraine and fibromyalgia. We used two automated methods to investigate whether morphometric changes occur in patients with rheumatoid arthritis (RA). Methods: We recruited 28 patients with severe RA, and 25 age- and sex-matched healthy controls. High-resolution MP-RAGE images were acquired on a 3T scanner Tim Trio (Siemens, Erlangen). Data were analyzed using FSL_VBM, a voxel-based morphometry style analysis and FreeSurfer, a surface-based morphometry. To investigate the effect of disease duration, a model with disease duration as a regressor of interest was used in the patients group. Results: There were no local structural grey-matter differences between patients and controls in the FSL_VBM. The FreeSurfer analysis however revealed decrease in grey-matter thickness in both parahippocampal gyri. Moreover, RA patients had significantly smaller brains compared to controls, estimated using intracranial volume (ICV). In the patient group, disease duration, when controlled for age, significantly correlated with ICV (r = 0.44 p = 0.019) and there was a trend for ASF (r = −0.36 p = 0.055). Furthermore, in the patients group the disease duration regressor negatively correlated with grey matter density in the thalamus. Conclusions: These results suggest that there are global brain differences associated with RA. However, it is not clear whether these changes represent an accelerated rate of atrophy as observed in fibromyalgia, the effect of systemic inflammation and vasculopathy similar to lupus erythrematosus or rathe